Body composition as indicator of eating disorders in female students - Olivera Pilipović-Spasojević; Nenad Ponorac; Mira Spremo (Биомедицинска истраживања, 2020)
Introduction: The transition to university education as a stressful period and the need to be likeable where physical appearance is concerned can be a trigger for a change in attitudes towards eating patterns. Body composition is an essential component of nutritional status and the most common parameter used as an indicator of physical appearance. An unobtrusive onset of eating disorder can easily lead to a preoccupation with eating and body weight. The aim of the paper is to determine whether the parameters of body composition can qualitatively detect respondents with eating disorders. Methods: The epidemiological observational and analytical study included a representative sample comprised of 408 healthy female students, aged 19-22 years. A short socio-demographic questionnaire, a standardized questionnaire for assessment of eating disorders-Eating Attitudes Test-26 were used in the study while Omron BF 510 was used for anthropometric measurements of body weight and BMI. Results: The sample consisted of female students: agedmean = 20.5 years, with average height 168.65 cm (SD = 6.01), body weight 63.09 kg (SD = 9.9) and BMI 22.1 (SD = 3.2). According to EAT-26 (Mean = 13.24 and SD = 7.97), 16.7% of respondents with risk factors for eating disorders were detected. Conclusion: The maximum value of the Youden index of 0.24 ROC analysis confirms that the body composition parameters are not reliable indicators of eating disorders and EAT-26 is not reliable and acceptable as an independent test for assessing risk factors by means of considering different attitudes and deviant eating behaviors. Therefore, in order to achieve detection, monitoring, and perform preventive action, it is necessary to conduct regular systematic examinations among the student population.
Keywords: eating disorder; body composition; female students